Effect of the Sea horse (Hipocampus kuda bleeker) Extract to the quantity and quality of spermatozoa of Mus musculus L - Trisnawati, Trisnawati (Syifa'Medika, 2011)
Sea horse (Hipocampus kuda bleeker) is believed to be a sexual stimulating substance. It is because the substance found in the extract contains aphrodisiac. Nevertheless, there is no whether the sea horse extracts from the male, female, or a combination of the two have effects on sexual functions. This research was aimed at investigating how the male, female, and combination sea horse extracts affected the quantity and quality of spermatozoa. This study applied the random design groups (RAK) with white mice (Mus musculus L) which were divided into seven groups in which each group had four white mice. The control group was given aquabidest while the experimental groups were given sea horse extract from male, female, or a combination of the two in which each was given a dosage of 250 and 300 mg/kg BB. The variables observed were the number of spermatozoa, morphology, motility, viability, and integrity of the plasma membrane of the spermatozoa. Data were analyzed by ANOVA test followed by Duncan test. The research finding of the 35 day treatment of the use of sea horse extract toward the white mice showed the giving of 300 mg/kg BB male sea horse extract and its combination with the female extract gave the best result toward the number of spermatozoa, morphology, and viability of spermatozoa. Integrity of spermatozo's plasma membrane increased when they were given the female sea horse extracts with the dosage of 250 mg/kgBB and the combination with the dosage 250 and 300 mg/kgBB. The variable of spermatozoa motility was not affected but there was increased increases of the average motility which was in line with the increase of dosage given. The conclusion was compared with the male sea horse extract, the female sea horse extract, and combination of the male and female sea horse extract significantly affected the quantity and quality of white mice's spermatozoa.